Company Purchase Decision Improvement Strategy - Ihdina Gustina; Dedy Lazuardi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine the effect of the Marketing Strategy on Purchasing Decisions at PT Pratama Mandiri Sakti. The research methodology used is quantitative descriptive method. The type of data used in this study is quantitative data, normally data obtained in the form of number or numbers. Data source are primary and secondary data . The result of analysis show that market segmentation and targeting has a significant and positive influence on PT. Pratama Mandiri Witness purchasing decisions based on the result of the partial hyphotesis test. The result showed that market segmentation and targeting had a significant effect on the PT. Pratama Mandiri Witness purchasing decisions and the remaining is influenced by other variables which was not examined.